Internet of things (IoT) based grid tension monitoring system - Lina Khalida, Norazmi (2022)
The objective of this project is to create a prototype of grid tension monitoring system for overhead transmission lines. A real-time monitoring system for grid tension overhead transmission line temperature, sag axis has been developed. As accidents are constantly being reduced and diagnoses are accelerating for automated grids, real time remote sensing and control is the configurations for smart grid implementation. In case of malfunction, the voltage and current exceed the operating limit, which requires in-time monitoring as well as diagnosis reporting. The project includes Internet of Things technology, which contributes to the monitoring of sensor readings, as well as an alert system that functions as a feedback system, responding to sensor readings by sending alerts to users on abnormal axis and temperature values. The project method relies on the transfer of data from the sensor module to the microcontroller, where it is recorded and displayed on a website and mobile application that users may access to monitor sensor readings. The Internet of things method use in this monitoring system is by using ThingSpeak web and Blynk application. Using the publish and monitor implementation, data is transmitted over the internet protocol. The algorithm must be constructed to identify the project input and output, as well as the procedures in between. The findings of the prototype showed a functional website and mobile application in which the digital display accurately displays readings in accordance with its intended purpose. However, the project lacks an additional dashboard with multifunctional readings, such as monitoring the quality of the sag and having issues with no independent battery support, which requires direct voltage supply.